MEDIASI PENAL PERSPEKTIF HUKUM PIDANA ISLAM - Rizal, Moch. Choirul (ULUL ALBAB Jurnal Studi Islam, 2017)
This conceptual study is to review two things. First, the penal mediation concept in perspective of Islamic criminal law. By outlining penal mediation as an alternative to the settlement of a criminal case out of court through a voluntary agreement between the victim and the perpetrator, then, at least, it is in accord with the concept of qishash-diyat and its punishment. Second, the contribution of the core idea of mediation penal in perspective of Islamic criminal law is for criminal law reform in Indonesia. In a review of these studies, the core idea of mediation penal in Islamic criminal law perspective fulfills the philosophical, juridical, and sociological aspects, so that the criminal law reform led to the strengthening and optimizing the penal mediation as an alternative to the settlement of the criminal case. The core ideas are: (1) the existence of penal mediation is necessary to set up first by legislation in Indonesia; (2) not all criminal offenses can be resolved through mediation penal; (3) there is no element of coercion on the involvement of both parties in conducting penal mediation; (4) the compensation agreed upon by the perpetrator and the victim or him/her family shall be given directly to victims or their families and not to the state; and (5) the completion of the criminal case by optimizing the penal mediation can abolish punishment for the perpetrators.